Sustainable manufacturing of next generation building materials using microwave energy - Calvo Carrascal, Miguel Angel (2018)
Global warming and the high energy demands of fossil fuel in industries have led governments to implement legislation aimed towards developing more energy efficient and sustainable processes. In the brickwork industry, the burning of coal and natural gas provides the energy to fire clay bricks in the 900-1200 oC range into high quality building materials. Microwaves powered by renewable energy sources have been suggested as a sustainable alternative to fossil fuels. Microwave heating has been considered a promising technique for the processing of clays due to the potential energy consumption and carbon footprint reductions, and for its volumetric heating nature, which enables the fast and uniform heating of a load. This could result in improving the mechanical properties of the fired products. The aims of this project were to develop an understanding of how microwaves interact with clays in order to show whether they could be used to fire clay-based building materials, and to understand how this could be achieved and the parameters that affect it.